Factors influencing prolactin levels in chronic long-term hospitalized schizophrenic patients with co-morbid type 2 diabetes mellitus - Zhu, Junhong; Wang, Huijuan; Huang, Shaoyun; Zhang, Yingying; Liu, Xuebing; Li, Yi; Ma, Jun (Frontiers in Psychiatry, 2022)
Background: For long-term hospitalized patients with schizophrenia, metabolic disease and hyperprolactinemia are common comorbidities. This article aimed to analyze the influencing factors of comorbid diabetes on prolactin levels in long-term hospitalized patients with schizophrenia. Methods: This study included 378 long-term hospitalized patients with schizophrenia. Common metabolic markers of included samples were collected, and the severity of psychopathology was assessed. The samples were divided into two groups based on the patients with or without diabetes mellitus. The differences in clinical parameters between the two groups were compared, and the effects of the parameters on the prolactin (PRL) level were analyzed. Results: Compared with non-diabetes patients, the patients in the co-diabetes group had lower PRL levels (P = 0.000) and more severe psychiatric symptoms (P = 0.016). Female, treated by risperidone, and high level of triglyceride were risk factors for PRL (B=26.31, t=5.39, P=0.000; B=19.52, t=4.00, P=0.000; B=2.71, t=2.31, P=0.022, respectively). Meanwhile, co-diabetes and aripiprazole were protective factors (B=15.47, t=3.05, P=0.002; B=-23.77, t=-2.47, P=0.014; respectively). Ultimately, in the co-diabetes group, we found that high dose of metformin was a protective factor for PRL (B=-0.01, t=-1.46, P=0.047), while female and aripiprazole were risk factors (B=16.06, t=3.26, P=0.001; B=20.13, t=2.57, P=0.011; respectively). Conclusion: Long-term hospitalization in patients with chronic schizophrenia is associated with more residual psychiatric symptoms and serious adverse reactions. We need more aggressive and effective interventions for adverse drug reactions in women and patients with co-diabetes. Metformin and aripiprazole are beneficial in patients with long-term chronic schizophrenia with low PRL levels.